2018
DOI: 10.1016/j.conbuildmat.2018.01.129
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate and acid resistance of lithomarge-based geopolymer mortars

Abstract: 2018). Sulfate and acid resistance of lithomarge-based geopolymer mortars. Construction and Building Materials, 166,[537][538][539][540][541][542][543][544][545][546][547][548][549][550][551][552][553] ABSTRACTThe resistance of room temperature cured geopolymer mortars (GPM) against chemical attacks, i.e. sodium and magnesium sulfate solutions, and sulfuric and hydrochloric acid solutions, was evaluated. GPMs were formulated using a lithomarge precursor (low-purity kaolin) to achieve 28-day characteristic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 74 publications
7
40
0
3
Order By: Relevance
“…It was seen from Figures that the samples in the salt solution do not suffer any damage and no color change. Similar to our work, although there are weight and length changes in the concrete produced by Kwasny et al, they have stated that there is no deterioration in the external appearance of the samples exposed to sulfate solutions for 52 weeks. Khan et al reported that in geopolymer concrete samples containing 70% BFS + 30% PC, there were fewer cracks and less visual deterioration than samples containing other binary binders.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It was seen from Figures that the samples in the salt solution do not suffer any damage and no color change. Similar to our work, although there are weight and length changes in the concrete produced by Kwasny et al, they have stated that there is no deterioration in the external appearance of the samples exposed to sulfate solutions for 52 weeks. Khan et al reported that in geopolymer concrete samples containing 70% BFS + 30% PC, there were fewer cracks and less visual deterioration than samples containing other binary binders.…”
Section: Resultssupporting
confidence: 91%
“…Ren et al produced samples metakaolin based geopolymer added wollastonite, tremolite, and short basalt fiber composition at different rates. Kwasny et al produced solid clay based geopolymer mortar samples with two different compressive strengths (37.5 and 60 MPa). The samples were immersed in 0.352 mol sodium sulfate and magnesium sulfate solutions for 52 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The zinc stearate mortar was the least affected with an increment of 7.7 points. These results are coherent with previous studies where it was observed that mortars exposed to acid attacks suffered mass ( Figure 6a) and strength losses (Figure 6b) due to the increase in porosity and permeability [47]. (Figure 6a) indicates that the higher the open porosity of the mortars, the higher is the mass loss.…”
Section: Mass Loss Caused By Sulphuric Acid Exposuresupporting
confidence: 92%
“…The mortar mix proportions used are presented in Table 3. The GP mixes are based on mix design optimisation carried out by Rafeet et al [43]- [45] and Vinai et al [19] and the PC mix proportions were obtained from work carried out by Kwasny et al [46]- [48]. The paste content was kept constant at 50% for all mortars, so that a fair comparison could be carried out between different mixes.…”
Section: Proportionsmentioning
confidence: 99%